2009
DOI: 10.1007/s11743-009-1165-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Surface Activity of Hexadecyl o‐Xylene Sulfonate Isomers

Abstract: This paper deals with the synthesis of a series of hexadecyl o-xylene sulfonate isomers (with the o-xylene ring located at different positions along the n-hexadecyl chain) by a Friedel-Crafts reaction, and the Grignard reaction followed by a hydrogenation. The structure was confirmed by 1 H NMR. All analytical methods indicated high levels of purities of the isomers with the orthoxylene ring located at the first, third, fifth and seventh carbon atom on the n-hexadecane chain. The critical micelle concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This result can be explained by the fact that the structure of the ARADS‐LAB surfactant is rather close to those of secondary alkysulfonates and sodium alkylsulfates, for which it is well known that the CMC values increase when the hydrophilic head moves to the internal positions of the alkyl chain (Myers, 1992). Qu et al (2010) reported that when the sulfonates group attached to the aromatic ring is moved to the center of the alkyl chain, a rise in CMC values is observed probably due to the diminution of the hydrophobic effect. Actually, in ARADS‐LAB, the disulfonate groups are randomly distributed along the alkyl chain and the secondary position isomers obtained by this process are about 92%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result can be explained by the fact that the structure of the ARADS‐LAB surfactant is rather close to those of secondary alkysulfonates and sodium alkylsulfates, for which it is well known that the CMC values increase when the hydrophilic head moves to the internal positions of the alkyl chain (Myers, 1992). Qu et al (2010) reported that when the sulfonates group attached to the aromatic ring is moved to the center of the alkyl chain, a rise in CMC values is observed probably due to the diminution of the hydrophobic effect. Actually, in ARADS‐LAB, the disulfonate groups are randomly distributed along the alkyl chain and the secondary position isomers obtained by this process are about 92%.…”
Section: Resultsmentioning
confidence: 99%
“…The high values of CMC and gamma γ CMC can be explained by the fact that the micellization is delayed due to the branching structure of the ARADS-LAB at the level of the hydrophilic head which is attached to two moieties of the alkyl chain, and which of the moieties carry the benzene ring, while in DDBS, the sulfonates group is directly linked to the aromatic ring. By taking into account the energetic aspect, when the branching of the hydrophobic chain is increased, this prevents the transfer of a surfactant molecule from the bulk to the interface (Qu et al, 2010). By comparing ARADS-LAB to LAS, it is found that γ CMC values are well compared at 298 K and are lower than that of DDBS at the same temperature, F I G U R E 1 Variation of the surface tension versus logarithm of concentration of ARADS-LAB at different temperatures but the CMC value is more important.…”
Section: Surface Tensionmentioning
confidence: 99%
“…The data are collected in Table 2. The CMC decreased with increasing alkyl chain length, probably because of the increasing hydrophobic effect [22,23].…”
Section: Surface Properties Of Npasmentioning
confidence: 99%